Determination of Quantum Yield for the Photochemical Decomposition of Dichloramine-B and Dibromamine-B in Aqueous Acetic Acid Medium. Issue 4 (2007) - Mohana, K. N.; Prasad, N.; Bhandarkar, P. M. Ramadas
Abstract : The photolysis of dihaloamines (RNX2 ), viz ., dichloramine-B (DCB) and dibromamine-B (DBB) in aqueous acetic acid (1:1 v/v) solutions has been studied with the UV light source (λ= 2537 Å). The experimental rate law obtained is - d [RNX2 ] / dt = k' Io / [RNX2 ], where Io is the intensity of incident light. The addition of benzenesulphonamide, the product of photolysis or uranyl ion had no significant effect on the rate of photochemical decomposition. A slight decrease in the rate has been observed by the addition of NaCl / NaBr to DCB / DBB solutions. The quantum yield (Φ) for the photolytic decomposition has been computed. A suitable photolytic mechanism and a rate law consistent with the observed results have been proposed.